AN INDEX REPRESENTING STRUCTURE-CATABOLIC FATE RELATIONSHIPS OF AMINO ACIDS (Journal of Sciences, Islamic Republic of Iran)
Based on the Randic suggestion of the resolution of a structure into shape, size, and function an index representing structure-catabolic fate relationships of amino acids is constructed. The index obtained by multiplying three factors; (nb2 + nr), nc and M; representing shape, size and function respectively, where nb2 = number of double bonds, nr = number of rings, nc = number of carbon atoms, and M = molecular weight. A systematics of amino acids is obtained and a correlation is observed between the index value and the catabolic fate.